Socialno varstveni zavod Hrastovec v razcepu med varstvom in varovanjem - Bohak, Tadeja (Psihološka obzorja (Ljubljana), 2017)
Following the enforcement of the Mental Health legislation in 2008, Hrastovec has been faced with new challenges and became the first social care home to have founded a so called secure unit. In line with the original mission of Hrastovec, the secure unit was dedicated to persons with multiple disabilities, including persons with difficulties in mental development as well as with long-term problems in mental health. After almost a decade, the original purpose of the secure unit has been challenged by the need to take care of post-forensic patients following the decision of the Court. The concerns that such patients are still dangerous to the society and that the unit does not have appropriate and specialized conditions, and thus cannot ensure appropriate safety for its users, remained unheard. Considering that the main purpose of Hrastovec is to provide social care for persons with special needs it seems that there is a need to make suitable changes for their benefit.
Keywords: socialno varstvo; duševno zdravje; mental health; forenzična psihiatrija; varovanje; Socialno varstveni zavod Hrastovec